2019
DOI: 10.1002/elan.201900582
|View full text |Cite
|
Sign up to set email alerts
|

Centri‐Voltammetric Folic Acid Detection

Abstract: The need for practical detection of folic acid (FA) has been increased day by day. For this reason in this work, a two steps electroanalytical technique, centri‐voltammetry was utilized for FA detection for the first time. In order to get rid of the slow electrode kinetics of FA oxidation, the working electrode was modified with graphene‐Pt hibrid nanomaterial. Also for increasing the sensitivity, 1‐Chloro‐2‐[2‐(2‐methoxyethoxy) ethoxy]ethane (TEG−Cl) and 1,2‐di{2‐[2‐(2‐methoxyethoxy)ethoxy] ethoxy}‐4‐nitroben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…FA plays a crucial role in the formation of red blood cells, body growth, and prevention of anemia. 37 39 As a significant biomolecule, the deficiency of FA leads to a number of chronic diseases including stroke, heart attack, psychosis, mentality devolution, neural tube disorder, and so forth, and a high dose may cause pernicious anemia. 40 , 41 Carbon dots derived from chemical precursors are explored by some researchers to trace this analyte.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FA plays a crucial role in the formation of red blood cells, body growth, and prevention of anemia. 37 39 As a significant biomolecule, the deficiency of FA leads to a number of chronic diseases including stroke, heart attack, psychosis, mentality devolution, neural tube disorder, and so forth, and a high dose may cause pernicious anemia. 40 , 41 Carbon dots derived from chemical precursors are explored by some researchers to trace this analyte.…”
Section: Introductionmentioning
confidence: 99%
“…M-CDs could detect folic acid, also known as vitamin B 9 , belonging to the group of water-soluble B group vitamins, with high specificity and sensitivity. FA plays a crucial role in the formation of red blood cells, body growth, and prevention of anemia. As a significant biomolecule, the deficiency of FA leads to a number of chronic diseases including stroke, heart attack, psychosis, mentality devolution, neural tube disorder, and so forth, and a high dose may cause pernicious anemia. , Carbon dots derived from chemical precursors are explored by some researchers to trace this analyte. Li et al have reported the synthesis of fluorescent carbon dots (CDs) for assaying FA by using citric acid and the ethylene imine polymer as precursors .…”
Section: Introductionmentioning
confidence: 99%
“…Generally in centri‐voltammetry, the analyte is accumulated onto the electrode surface via centrifugation and then immediate voltammetric scan is applied. In order to obtain more efficient deposition of the analyte, sometimes a suitable carrier has also been used [48,49] . As a result more sensitive analysis has been done [50–53] .…”
Section: Introductionmentioning
confidence: 99%
“…However, at high centrifuge speeds, this situation can have the opposite effect and can cause the disintegration of the resulting film and as a result movement of the analyte away from the electrode surface. After adsorption procedure for 7 min, in order to investigate this effect, 1000, 2000, 3000, 4000 and 5000 rpm of the centrifugation speeds were applied to the centri‐voltammetric cell that contained 5 mM GSH, 1 μL PDI−C 4 SH carrier molecule for 4 min [48] . As a result, the maximum peak current was obtained at 4000 rpm where a decrease in the peak current was detected at higher centrifuge speeds because of the analyte dissipation from the active electrode surface (Figure 4c,d).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation